ROLE OF SERUM ALANINE AMINOTRANSFERASE IN TYPE -2 DIABETES MELLITUS - VASANTHAN.M.; SUMATHI.K. (International Journal of Pharma and Bio Sciences, 2013)
Liver disease is a very common disease world-wide not only among the alcoholics but also frequently among the non-alcoholic population due to various other risk factors like drug abuse, systemic hypertension, diabetes etc. The aim of this study is to show the increased level of alanine amino transferase in poor glycemic controlled diabetics. This study includes 27 diabetics not under glycemic control with HbA1clevels above 7 and 23with HbA1clevels below 7 showing a good glycemic control. Serum alanine amino transferase was estimated by enzymatic (kinetic) method and HbA1c by ion exchange chromatography. Out of 27 poorly controlled diabetics, 19 had increased serum alanine aminotransferase which is significant. It is concluded from this study that diabetes may lead to liver damage, which implicates the importance of having good glycemic control. It is also mandatory to screen the diabetics particularly those not under glycemic control by estimating ALT which is a sensitive hepatocyte marker.